Development of Uno Stacko Games-Based Learning Media Integrated with Qr Code on the Material of the Human Respiratory System in Increasing Interest and Understanding of Concepts for Grade VIII Middle School Students - Yunimuninggar, T. D.; Fardhani, I. (Universitas Negeri Yogyakarta, 2024)
Game-based learning media is a media that can improve students' interest and conceptual understanding effectively. In this study, the research and development (R&D) method was used by adopting the ADDIE model to develop a learning media based on Uno Stacko game with a focus on the topic of Respiratory System which was integrated with the QR Code. The effectiveness test that was used on the learning media was a quasi-experimental design. The media testing used three classes consisting of a trial class with a total of 25 students, as well as a control class and an experimental class, each of which consisted of 23 students. The results of the study of the students' learning interest with the Respiratory System Uno Stacko learning media along with further explanation by the teacher using the lecture method differ significantly from the learning interest of the students who only used the lecture method. The implementation of the learning media can improve learning interest. It can be seen from the result of the average percentage of the experimental class with a total of 81% which is higher than the control class with a total of 76